Catalytic oxidative cyclisation reactions of 1,6-enynes: a critical comparison between gold and palladium - Nunes dos Santos Comprido, Laura; Hashmi, A. Stephen K. (Israel journal of chemistry, 2013)
In transition-metal catalysis, similar reactivities are often described for related metals, thereby resulting in the formation of similar/identical products. However, only in rare cases can similar/identical product be obtained by using non-related metals. Amongst these reactions is the oxidative cyclisation of 1,6-enynes by using palladium or gold. Similarities and differences will be discussed with a special focus on the diastereo- and enantioselective course of the reaction.